2012
DOI: 10.1245/s10434-012-2535-8
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase 1 Expression is Associated with Poor Prognosis in Patients with Esophageal Squamous Cell Carcinoma

Abstract: ALDH1 was found to be a predictor of postoperative recurrence and prognosis in ESCC, and CD44 might be a predictor of recurrence and prognosis. ALDH1 expression might affect the treatment strategy for ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…The by‐products of this metabolic process increase the self‐renewal ability of mesenchymal stem cells . ALDH1 activity is found in neoplastic cells, which show proliferative ability similar to that observed in stem cells and tumors with aggressive clinical behavior .…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The by‐products of this metabolic process increase the self‐renewal ability of mesenchymal stem cells . ALDH1 activity is found in neoplastic cells, which show proliferative ability similar to that observed in stem cells and tumors with aggressive clinical behavior .…”
Section: Introductionmentioning
confidence: 79%
“…Highly tumorigenic cancer stem‐like cells present in HNSCC have been considered responsible for the aggressive biological behavior of this tumor . Most studies available in the literature describe the use of cell culture techniques, flow cytometry, or transplantation assays in animal models to detect highly tumorigenic cells and thus assess the pathobiology of HNSCC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, BMI1 overexpression was correlated to advanced pathological stage and lymph node metastasis in ESCC and EAC [102,103]. Clinical studies have also revealed that EpCAM [95,104], ABCG2 [100], ALDH1 [96,105], NANOG [106], GLI1 [107,108], and CD24 [109] could be considered as CSC markers in ESCC, since their expression was associated with clinicopathological characteristics of tumors.…”
Section: Esophagusmentioning
confidence: 98%
“…Furthermore, the expression of OCT4 and SOX2 was significantly associated with higher histological grade and poorer survival of ESCC [93,94]. In addition, expression of CD133 [82] and CD44 [79,95,96], specifically CD44v6 [97,98], was associated with clinicopathological features of ESCC and EAC, although a number of studies reported contradictive results [99][100][101]. In addition, BMI1 overexpression was correlated to advanced pathological stage and lymph node metastasis in ESCC and EAC [102,103].…”
Section: Esophagusmentioning
confidence: 99%